Impact of patient characteristics on the clinical efficacy of mongersen (GED‐0301), an oral Smad7 antisense oligonucleotide, in active Crohn's disease. Issue 6 (13th January 2016) - Monteleone, G.; Di Sabatino, A.; Ardizzone, S.; Pallone, F.; Usiskin, K.; Zhan, X.; Rossiter, G.; Neurath, M. F.
Summary: Background: In a phase 2 study, mongersen, an oral antisense oligonucleotide targeting Smad7, was effective in inducing clinical remission in approximately 60% of patients with active Crohn's disease (CD). Aim: In a post hoc analysis to evaluate those patient disease characteristics that may have influenced the efficacy and safety of mongersen therapy. Methods: Patients with steroid‐dependent/resistant, active CD were randomised to mongersen 10, 40 or 160 mg/day or placebo for 2 weeks; patients were followed for 10 weeks. Clinical remission [Crohn's Disease Activity Index (CDAI) score <150] and clinical response (CDAI score reduction ≥100 points) were assessed at weeks 2, 4 and 12 for these subgroups: disease duration <5/≥5 years, human serum C‐reactive protein (hsCRP) <3/≥3 mg/L, and CDAI at baseline ≤260/>260. Additional patient baseline and disease characteristics were explored. Results: Clinical remission and response rates were significantly higher in patients receiving mongersen 40 and 160 mg/day but not 10 mg/day vs. placebo and independent of disease duration and hsCRP. Patients with baseline CDAI ≤260 had significantly higher remission rates with 40 and 160 mg/day. In patients with baseline CDAI >260, remission rates were statistically greater with 160 mg/day and numerically better with 40 mg/day vs. placebo. Adverse event rates were similar across treatment groups. Mongersen was safe and well tolerated. Conclusions: Patients with higher CDAI scores achieved clinical remission most frequently with the highest mongersen dose. Disease duration and baseline human serum C‐reactive protein did not appear to significantly impact efficacy of mongersen in this study (EudraCT Number: 2011‐002640‐27.)